2018
DOI: 10.1136/sextrans-2017-053357
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of community-level human papillomavirus vaccination coverage in aschool-based vaccination programme

Abstract: Across all three doses, there are notable variations by socioeconomic status, with steep reverse gradients in three socioeconomic indicators. More quantitative and qualitative research needs to be conducted to determine the effects of the 2014 transition from a three-dose regimen to two-dose regimen on vaccination coverage, especially in groups that experience lower rates of vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In England, Jan et al showed that LHUs with more educational deprivation had higher rates of vaccination for all doses. In this study, educational deprivation includes individuals with no qualification or the lowest levels of qualification [ 12 ]. On the other hand, in Greece, Michail et al observed that female students who studied at university were more likely to be vaccinated than female students who attended a Technological Institute [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In England, Jan et al showed that LHUs with more educational deprivation had higher rates of vaccination for all doses. In this study, educational deprivation includes individuals with no qualification or the lowest levels of qualification [ 12 ]. On the other hand, in Greece, Michail et al observed that female students who studied at university were more likely to be vaccinated than female students who attended a Technological Institute [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…While acceptance of personal susceptibility to a condition also believed to be serious was held to produce a force leading to behaviour, the particular course of action to be taken depends upon beliefs regarding the effectiveness of the various actions available in reducing the disease threat [ 11 ]. Evaluation of the perceptions about benefits, barriers, severity and susceptibility of HPV vaccines could play a key role in the development of targeted educational campaigns that would increase the intention to get the HPV vaccine [ 12 , 21 ]. Public Health professionals should provide tailored information to reinforce strength of recommendations regarding HPV vaccination, especially with parents of young women [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In England Jan S, et al showed that LHU with more educational deprivation had higher rates of vaccination for all doses. In this study educational deprivation includes individuals with no qualification or the lowest levels of qualification [12]. On the other hand, in Greece Michail G et al observed that female students who studied at University were more likely to be vaccinated than female students who attended a Technological Institute [13].…”
Section: Discussionmentioning
confidence: 95%
“…While acceptance of personal susceptibility to a condition also believed to be serious was held to produce a force leading to behaviour, the particular course of action to be taken depends upon beliefs regarding the effectiveness of the various actions available in reducing the disease threat [11]. Evaluation of the perceptions about benefits, barriers, severity and susceptibility of HPV vaccine could play a key role in the development of targeted educational campaigns that would increase the intention to uptake the HPV vaccine [12,21]. Public Health professionals should provide tailored information to reinforce strength of recommendation regarding HPV vaccination, especially with parents of young women [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of serotypes,4 school-based access to vaccination,5 vaccination uptake in clinic populations of men who have sex with men6 and population prevalence rates7 continue to present challenges for implementation science in a complex global picture.…”
mentioning
confidence: 99%